Fundamental study of high Q‐factor RF spiral inductor using carbonyl‐iron/epoxy composite magnetic core. (17th June 2016) - Sonehara, Makoto; Furihata, Kazuaki; Koguchi, Jun; Tanaka, Shingo; Sato, Toshiro
Abstract : In order to increase the Q ‐factor of an RF spiral inductor used in the RF front‐end circuit of smartphone handsets, we introduced a carbonyl‐iron/epoxy composite magnetic core in the air‐core spiral inductor. The composite magnetic core, which was made by metal‐mask printing, consisted of carbonyl‐iron powder of 1.1 μ m mean diameter and an epoxy resin matrix. We found that the 45 vol.% CIP composite magnetic core had a saturation magnetization of 0.9 T, relative permeability of ∼6, and loss tangent (tan δ ) of ∼0.2 at 1 GHz. A two‐turn copper spiral inductor fabricated with the composite magnetic core filled only in the spacing between the conductor lines showed a clear Q ‐factor increase of ∼29% compared to the air‐core spiral inductor at 1 GHz. Thus we obtained a substantial increase in the Q ‐factor by the embedded composite magnetic core in the spacing between the conductor lines. The main reason for this is that the magnetic flux passing through the conductor lines was decreased by the magnetic core embedded in the spacing between conductor lines as a result of the magnetic flux passing mainly through the embedded magnetic core. Therefore, proximity effect is suppressed in the conductor line of the spiral coil. © 2016 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.